RippleFPGA: A routability-driven placement for large-scale heterogeneous FPGAs - Chak-Wa Pui; Gengjie Chen; Wing-Kai Chow; Ka-Chun Lam; Jian Kuang; Peishan Tu; Hang Zhang; Young, Evangeline F. Y.; Bei Yu (Digest of technical papers - IEEE/ACM International Conference on Computer-Aided Design, 2016)
As the complexity and scale of FPGA circuits grows, resolving routing congestion becomes more important in FPGA placement. In this paper, we propose a routability-driven placement algorithm for large-scale heterogeneous FPGAs. Our proposed algorithm consists of (1) partitioning, (2) packing, (3) global placement with congestion estimation, (4) window-base legalization, and (5) routing resource-aware detailed placement. Experimental results show that our proposed approach can give routable placement results for all the benchmarks in the ISPD2016 contest and can achieve good result compared to the other wining teams of the ISPD2016 contest.